Pore-scale modeling of multiphase flow through porous media under triaxial stress. (December 2018) - Fagbemi, Samuel; Tahmasebi, Pejman; Piri, Mohammad
Highlights: A coupled geomechanical model for multiphase flow modeling. Numerical coupling of the effect of external force and fluid drag force. Permeability and fluids distributions are analyzed under various external forces. Abstract: In reality, most of the fluid and rock interactions occur in the presence of multiple fluid phases. Such exchanges, thus, are very important when different fluids, under the influence of external forces, coexist in the pore space. In this work, the response of Berea sandstone under quasi-static loading conditions is modeled in the presence of multiple fluid phases. The solid matrix is characterized by hyperelasticity, while the fluids are assumed to be incompressible and Newtonian. The behavior of the sample was investigated during the exertion of confining stresses at the grain boundaries followed by a sequence of drainage and imbibition cycles, using the Volume of fluid (VOF) method, to investigate the effect of triaxial loading on fluid distribution. We further investigated the role of stress on relative permeability, initial water saturation, residual oil saturation and trapped oil globule size distribution. Our results indicate relative permeability alteration due to compaction and changes in the pore geometry. Relative permeability of the oil phase during drainage was reduced, while there was a slight decrease in relative permeability of water. Furthermore, the initial water saturation increased due to a general shift in the pore/throat diameter distribution towards smaller values leading to the wetting phase occupying more pore throats. Finally, higher confining stress conditions resulted in a greater distribution of disconnected oil globules compared to a smaller distribution of globules at zero stress conditions.